The interaction of sterically stabilized magnetic nanoparticles with fresh human red blood cells - Pham BTT (Dove Medical Press, 2015)
Binh TT Pham,1 Nirmesh Jain,1 Philip W Kuchel,2 Bogdan E Chapman,2,† Stephanie A Bickley,3 Stephen K Jones,3 Brian S Hawkett11School of Chemistry, University of Sydney, 2School of Molecular Bioscience, University of Sydney, 3Sirtex Medical Limited, Sydney, NSW, Australia†Bogdan E Chapman passed away on August 16, 2014Abstract: Sterically stabilized superparamagnetic iron oxide nanoparticles (SPIONs) were incubated with fresh human erythrocytes (red blood cells [RBCs]) to explore their potential application as magnetic resonance imaging contrast agents. The chemical shift and linewidth of 133Cs+ resonances from inside and outside the RBCs in 133Cs nuclear magnetic resonance spectra were monitored as a function of time. Thus, we investigated whether SPIONs of two different core sizes and with three different types of polymeric stabilizers entered metabolically active RBCs, consuming glucose at 37°C. The SPIONs broadened the extracellular 133Cs+ nuclear magnetic resonance, and brought about a small change in its chemical shift to a higher frequency; while the intracellular resonance remained unchanged in both amplitude and chemical shift. This situation pertained over incubation times of up to 90 minutes. If the SPIONs had entered the RBCs, the intracellular resonance would have become broader and possibly even shifted. Therefore, we concluded that our SPIONs did not enter the RBCs. In addition, the T2 relaxivity of the small and large particles was 368 and 953 mM-1 s-1, respectively (three and nine times that of the most effective commercially available samples). This suggests that these new SPIONs will provide a superior performance to any others reported thus far as magnetic resonance imaging contrast agents.Keywords: 133Cs NMR spectroscopy, bulk magnetic susceptibility, fresh human erythrocyte, particle stability, paramagnetic shift, superparamagnetic iron oxide nanoparticles, SPIONs